Predictive Value of Protein Kinase C Delta as a Diagnostic Biomarker for Hepatocellular Carcinoma in Hepatitis C Virus-Related Cirrhosis - Amer, Heba; Elfakhry, A; Abd El-Hafez, Afaf; El Arman, Mohammed M; Abozeid, Fatma (Scripta Medica, 2026)
Background/Aim: Hepatocellular carcinoma (HCC) is considered the 6th prevalent tumour and 3rd leading cause of cancer-associated mortality worldwide. Protein kinase C delta (PKCδ), released by liver cancer cells, has an effect in cell-proliferation and cancer formation, recommending PKCδ can serve as a good biomarker in HCC detection. The aim of this research was the assessment of predictive value of PKCδ as a diagnostic biomarker for HCC in hepatitis C virus (HCV)-related cirrhosis. Methods: The study involved 180 participants, who were separated into three groups, the first control group included 45 healthy volunteers, the second cirrhotic without HCC group (non-HCC group) included 45 cirrhotic patients due to HCV and the third cirrhotic with HCC group (HCC group) included 90 cases with HCC on top of HCV-related cirrhosis. All participants were subjected to clinical examination, taking of history, radiological evaluation and routine laboratory investigations involving alpha-fetoprotein (AFP) assessment. PKCδ was assessed for all participants using Enzyme-Linked Immunosorbent Assay. Results: AFP and PKCδ concentrations were greater in HCC than in non-HCC and controls. PKCδ ≥ 30.75 ng/mL showed excellent diagnostic performance for detecting HCC in HCV-related cirrhosis (AUC = 0.977, sensitivity 95.6 %, specificity 86.7 %, accuracy 92.6 %). Multivariate analysis identified PKCδ ≥ 30.75 ng/mL, AFP ≥ 9.4 ng/mL and current smoking as independent predictors of HCC. Conclusion: PKCδ has a significant diagnostic ability for hepatocellular carcinoma (HCC), with good specificity and sensitivity in HCC prediction in patients with HCV-related liver cirrhosis.